Serosurvey of antibodies against zoonotic pathogens in free-ranging wild canids (Cerdocyon thous and Lycalopex gymnocercus) from Southern Brazil. (December 2021) - Padilha, Thamiris Cardoso; Zitelli, Larissa Caló; Webster, Anelise; Dall'Agnol, Bruno; Rosa, Verônica Bueno da; Souza, Ugo; Peters, Felipe Bortolotto; Jardim, Márcia; Trigo, Tatiane Campos; Rodrigues, Rogério Oliveira; Marks, Fernanda Simone; Reck, José
Abstract: The expansion of urbanization on natural areas is increasing contact between human populations with wild animals. Wild carnivores can act as sentinel hosts or environmental health indicators. Thus, the aim of this work was to investigate the exposure of two major species of wild canids from Southern Brazil to selected pathogens. For that, we live-trapped free-ranging Cerdocyon thous and Lycalopex gymnocercus in five localities and determined the frequency of animals with antibodies against Toxoplasma gondii, Trypanosoma cruzi, Leishmania infantum, Neospora caninum, and Leptospira spp. Among the canids sampled, 23% (12/52) (95%CI: 13–36%) had antibodies against T. gondii, with titers ranging from 64 to 512 . For T. cruzi, 28% (15/52) (95%CI: 18–42%) of sampled canids were seropositive, with titers ranging from 8 to 64. Concerning the protozoan pathogen N. caninum, a total of 5% (3/52) (95%CI: 2–15%) of wild canids had antibodies against it. None of the sampled canids showed the presence of antibodies against L. infantum . On the other hand, 44% (23/52) (95%CI: 31–57%) of the wild canids showed antibodies against Leptospira spp. The set of results presented here, show that free-ranging neotropical wild canids are exposed and have antibodies against to T. gondii, T. cruzi, Leptospira spp., and to a lesser degree to N. caninum . We found no evidence of L. infantum circulation among the studied populations. These results highlight some of the major pathogens which may represent risks for populations of these wild canids. Data Availability Statement: The data that support the findings of this study are available from the corresponding author upon reasonable request. Highlights: Wild canids are major reservoirs of infectious diseases. Few studies have addressed pathogens of Lycalopex gymnocercus . Toxoplasma gondii and Leptospira spp. seem widespread among wild canids. A third of canids were seropositive for Trypanosoma cruzi . Neospora caninum seems rare, contrarily to North America.